High-level swimmer perceptions of motivation and resilience - Karvonen, E. M. (Grand Canyon University, 2024)
The purpose of this qualitative, descriptive study was to describe the influential experiences that reinforced the development of high levels of motivation, and high lebels of resilience which impacted their careers, in high-level swimmers from different countries. Theoretical foundations guiding this study were self-determination theory (SDT) and Grit. SDT gave a framework for the development of motivation, while Grit described the personality characteristics allowing the development of resilience. The research questions were: How do high-level swimmers describe their experiences oft he development of motivation and its impact upon their athletic careers? How do high-level swimmers describe their experiences oft he development of resilience and its impactupon their athletic careers? The sample was 45 high-level international athletes. Data was collected by a questionnaire and semi-structured interviewst o identify themes about the development and impact of motivation and resilience. Thematic analysis was used in the analysis to draw out themes that describe the development and impacts of motivation and resilience. The findings of this study suggest that high-level swimmers' motivation is built through early positive influences igniting intrinsic motivation, fueled by process and mastery-oriented mindset. Resilience is biult through negative experiences throughout their swimming careers and from finding suitable coping mechanisms to continue swimming at a high level. Recommendations for future research, including longitudinal studies, comparative analysis between different sports and genders, and using more advanced analytical methods are presented.